2017
DOI: 10.1111/cdep.12227
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Syndromes and Developmental Risk for Autism Spectrum and Attention Deficit Hyperactivity Disorders: Insights From Fragile X Syndrome

Abstract: Many genetic markers are associated with atypical developmental outcomes. In this article, we review evidence from studies on the most common inherited cause of intellectual disability, fragile X syndrome (FXS). We aim to highlight general developmental consequences as well as specific implications for autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), including the complexity of characterizing ASD and ADHD symptoms in FXS. We address three issues: First, links among genes, bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…FXS, with around one-third of those with FXS also having an autism diagnosis (Doherty & Scerif, 2017;Kaufmann et al, 2017). Formal diagnostic assessment for autism should be considered (although may not be necessary) for all children with FXS.…”
Section: Gebhardt Et Al 2020) Autism Is Frequently Diagnosed In Child...mentioning
confidence: 99%
“…FXS, with around one-third of those with FXS also having an autism diagnosis (Doherty & Scerif, 2017;Kaufmann et al, 2017). Formal diagnostic assessment for autism should be considered (although may not be necessary) for all children with FXS.…”
Section: Gebhardt Et Al 2020) Autism Is Frequently Diagnosed In Child...mentioning
confidence: 99%
“…Of note, further valuable insights can come from neurodivergent individuals for whom symptoms of autism and attention differences cluster together. Fragile X syndrome (FXS) is the most common genetically identified and inherited monogenic syndrome associated with a high prevalence of autistic and ADHD symptoms (Doherty & Scerif, 2017). By tracking autism and ADHD symptoms longitudinally over the course of 3 years across a diverse group of children and teenagers with FXS, Doherty et al (2020) found that individual variation in ADHD symptoms predicted later individual variation in autism symptoms, bolstering the need to investigate more precisely how attention, activity levels, and autistic characteristics interact over developmental time.…”
Section: Neurodiversitymentioning
confidence: 99%
“…The evidence on the association between comorbidity and severity of a disorder could also be easily explained from this dimensional approach (Casey et al, ) as follows: the greater the number of domains (and the constructs within those domains) altered the more severe the disorder. As Neuroconstructivism suggests, it is necessary to move the focus from the double dissociations (the premium evidence for static, classical models) to the associations between syndromes; the different neurodevelopmental disorders are placed in the continuum in relation to different functions (Doherty & Scerif, ; Karmiloff‐Smith, Scerif, & Ansari, ); the intervention would be then guided by the support needs in relation to each function rather than by a particular categorical diagnosis.…”
Section: Dimensional Approach: Looking At the Whole Range Of Variationmentioning
confidence: 99%